During and After Study Abroad Period: Perception and Attitudes on English Development and Maintenance - Rahayu, Dwi (Journal of English Language Teaching and Linguistics, 2021)
This study examines the development and maintenance of English skills from the perspective of higher education alumni during and after studying abroad. The researcher consider attitudes, more specifically how, what, and to what extent attitudes could encourage development and maintenance in the context of study abroad from the 120 respondents’ perspective. This study deploys quantitative data collection in form of a survey with both multiple choice items and open-ended questions. The numeric items were analyzed with tabulation and the open-ended questions responses were analyzed with the stages of Thematic Analysis. Foremost, the findings reveal that the respondents perceive oral production and fluency as the major skills that improved during the study abroad period, followed by an increase in vocabulary knowledge and listening skills. Most respondents regarded the improvement as an influence of high exposure to spoken English. Secondly, the majority of respondents conceive that their English keeps improving after the study abroad period. The most frequent reasons for using English are social life and entertainment purposes, which are mostly individual preferences, followed by academic purposes such as joining a course or working on journal articles. Work purpose, surprisingly, is not the main reason of using English after study abroad period. The conclusion is that study abroad benefits the respondents in developing their English and that attitude on affective domain (how we perceive a language) and conative (behaviour toward a language) help to maintain the cognitive domain (knowledge on a language) and its maintenance.